Assessing learning as a possible sign of consciousness in post-coma persons with minimal responsiveness - Lancioni, Giulio E.; Bosco, Andrea; Olivetti belardinelli, Marta; Singh, Nirbhay N.; O’Reilly, Mark F.; Sigafoos, Jeff; Buonocunto, Francesca; Navarro, Jorge; Lanzillotti, Crocifissa; D'Amico, Fiora; De Tommaso, Marina (Frontiers in Human Neuroscience, 2014)
A learning test procedure based on operant principles may be useful in the diagnosis (and eventually rehabilitation) of post-coma persons with minimal responsiveness. This study was aimed at extending the evaluation of such a procedure with seven participants who presented with very limited behavior and apparently severe disorders of consciousness. The procedure was evaluated through an ABACB design, in which A represented baseline phases without stimulation, B intervention phases with brief stimulation periods contingent on specific responses of the participants, and C a control phase in which stimulation was available all the time. Increased responding during the B phases, as opposed to the A and C phases, was taken to indicate learning and possibly a non-reflective expression of phenomenal consciousness. All participants were also evaluated with the Coma Recovery Scale-Revised (CRS-R) prior to the start of the learning test procedure and at the end of it. The results of the learning test showed that all participants had significantly higher responding levels during the B phases. The CRS-R scores suggested minimally conscious state for four of them prior to the learning test and for five of them after the completion of the learning test. The implications of the findings are discussed in terms of potential and time cost of the learning test.